Eletrocardiografia contínua (Holter) na avaliação de cães com degeneração mixomatosa crônica da valva mitral - Maira Souza de Oliveira (2009)
Degenerative mitral valve disease (DMVD) is by far the most common cardiovascular disease in dogs. This study shows us the results of the clinical, electrocardiographical (ECG), echocardiographical and Holter recording exams performed in 40 small breed dogs (mean of 8,31 kg), greater than six years old (mean of 7,8 years old). There were 10 clinically normal dogs and 30 with DMVD categorized into three classes of congestive heart failure (CHF). On the two-dimensional echocardiography, the left atrium was evaluated and measured for dilatation, presenting statistical difference among the three classes of CHF, indicating greater values according to the progression of the disease. Some echocardiographic parameters were used to formulate a linear equation classificating dogs into healthy and having mild, moderate and severe mitral valve insufficiency. Arrhythmias that were not detected in ECG evaluation were diagnosed by Holter recording. Time-domain analysis of the heart rate variability showed decreased values as long as the DMVD progresses, being statistically significant for severe mitral valve insufficiency dogs. Frequency -domain analyses resulted in an increasing on the LF/HF values. Both analyses indicated enhanced sympathetic and decreased parasympathetic tone due to DMVD and CHF. Thus, considering the results obtained with Holter recording, it was possible to establish prognosis parameters for dogs with DMVD